Question
upstudy study bank question image url

\( 3.1 \frac{\left(4 x^{2} y^{3}\right)^{3}}{x^{4} y} \) as \( x=-2 \) en \( y=-1 \)

Ask by Willis Mcfarlane. in South Africa
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

When \( x = -2 \) and \( y = -1 \), the expression \( 3.1 \frac{\left(4 x^{2} y^{3}\right)^{3}}{x^{4} y} \) equals 793.6, which is the same as \( \frac{3968}{5} \) or \( 793\frac{3}{5} \).

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

Beyond the Answer

Laten we de uitdrukking eerst vereenvoudigen. We hebben \( 3.1 \frac{\left(4 x^{2} y^{3}\right)^{3}}{x^{4} y} \). Eerst berekenen we \( \left(4 x^{2} y^{3}\right)^{3} \): \[ = 4^{3} (x^{2})^{3} (y^{3})^{3} = 64 x^{6} y^{9} \] Nu vervangen we dit in de oorspronkelijke uitdrukking: \[ 3.1 \frac{64 x^{6} y^{9}}{x^{4} y} = 3.1 \cdot 64 \cdot \frac{x^{6}}{x^{4}} \cdot \frac{y^{9}}{y} \] Door de exponenten te vereenvoudigen: \[ = 3.1 \cdot 64 \cdot x^{2} \cdot y^{8} \] Nu substitueren we \( x = -2 \) en \( y = -1 \): \[ = 3.1 \cdot 64 \cdot (-2)^{2} \cdot (-1)^{8} \] Bereken dit: \( (-2)^{2} = 4 \) en \( (-1)^{8} = 1 \), dus: \[ = 3.1 \cdot 64 \cdot 4 \cdot 1 = 3.1 \cdot 256 = 793.6 \] De uiteindelijke waarde van de uitdrukking is \( 793.6 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy